An effective strategy to diagnose HIV infection: findings from a national audit of HIV partner notification outcomes in sexual health and infectious disease clinics in the UK. (5th August 2016) - Rayment, Michael; Curtis, Hilary; Carne, Chris; McClean, Hugo; Bell, Gill; Estcourt, Claudia; Roberts, Jonathon; Wilkins, Ed; Estreich, Steven; Morris, Georgina; Phattey, Jara; Sullivan, Ann K
Abstract : Objectives: Partner notification (PN) is a key public health intervention in the control of STIs. Data regarding its clinical effectiveness in the context of HIV are lacking. We sought to audit HIV PN outcomes across the UK. Methods: All UK sexual health and HIV services were invited to participate. Clinical audit consisted of retrospective case-note review for up to 40 individuals diagnosed with HIV per site during 2011 (index cases) and a review of PN outcomes for up to five contacts elicited by PN per index case. Results: 169/221 (76%) clinical services participated (93% sexual health/HIV services, 7% infectious diseases/HIV units). Most (97%) delivered PN for HIV. Data were received regarding 2964 index cases (67% male; 50% heterosexual, 52% white). PN was attempted for 88% of index cases, and outcomes for 3211 contacts were audited (from an estimated total of 6400): 519 (16%) were found not to be at risk of undiagnosed HIV infection, 1399 (44%) were informed of their risk and had an HIV test, 310 (10%) were informed of the risk but not known to have tested and 983 (30%) were not informed of their risk of HIV infection. Of 1399 contacts tested through PN, 293 (21%) were newly diagnosed with HIV infection. Regular partners were most likely to test positive (p<0.001). Conclusions: HIV PN is a highly effective diagnostic strategy. Non-completion of PN thus represents a missed opportunity to diagnose HIV in at-risk populations. Vigorous efforts should be made to pursue PN to identify people living with, and at risk of, HIV infection.